Peningkatan Daya Saing UMKM Pengrajin Telur Asin Pesurungan Lor Melalui Pemasaran Digital dan Manajemen Usaha - Krisdiyawati, Krisdiyawati; Kamal, Bahri; Amaliyah, Fitri; Hasan, Imam (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service activity aims to improve the competitiveness of Pesurungan Lor Tegal salted egg craftsmen's MSMEs through digital marketing and business management. The method of implementing the community service uses interactive counseling by interacting, asking, discussing, or practicing directly. The community service evaluation instrument uses a questionnaire in the form of a pre-test and post-test and is analyzed descriptively. The results of this community service show an increase in knowledge and understanding of digital marketing and business management in an effort to build awareness of MSME Salted Egg Craftsmen to run their businesses more developed. MSME actors have also understood the benefits and used several online market ceilings (e-marketplaces) in supporting their business and business management. MSME actors believe that the support for the use of digital marketing and business management can improve their business.